2009
DOI: 10.1007/s10529-009-0048-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nitrogen removal in bio-electrochemical systems by pH control

Abstract: Microbial fuel cells can be designed to remove nitrogenous compounds out of wastewater, but their performance is at present limited to 0.33 kg NO(3) (-)-Nm(-3) net cathode compartment (NCC) d(-1). By maintaining the pH in the cathode at 7.2, nitrogen removal was increased from 0.22 to 0.50 kg NO(3) (-)-Nm(-3) NCC d(-1). Bio-electrochemical active microorganisms seem to struggle with the deterioration of their own environment due to slow proton fluxes. Therefore, the results suggest that an appropriate pH adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 18 publications
7
50
0
Order By: Relevance
“…Clauwaert et al (2009) found that nitrogen removal was increased from 0.22 to 0.50 kg NO 3 − N m −3 NCC day −1 by maintaining the pH in the cathode chamber at 7.2. During the carbon and nitrogen removal process, production of protons at the anode and consumption of protons at the cathode may cause a pH drift, and this is expected to inhibit the biofilm activity.…”
Section: Optimization Of Operational Conditionsmentioning
confidence: 97%
“…Clauwaert et al (2009) found that nitrogen removal was increased from 0.22 to 0.50 kg NO 3 − N m −3 NCC day −1 by maintaining the pH in the cathode chamber at 7.2. During the carbon and nitrogen removal process, production of protons at the anode and consumption of protons at the cathode may cause a pH drift, and this is expected to inhibit the biofilm activity.…”
Section: Optimization Of Operational Conditionsmentioning
confidence: 97%
“…A cation exchange membrane (CEM) (Ultrex CMI7000, Membranes International Inc.) was used between the anodic and cathodic frames. As electrolyte for anode and cathode a minimal medium, consisting of 6 g Na 2 HPO 4 Á2H 2 O l -1 , 3 g KH 2 PO 4 l -1 , 0.1 g (NH 4 ) 2 PO 4 l -1 , 0.1 g Ca(PO 4 ) 2 l -1 and 0.5 ml l -1 of a tracemetal solution previously described by Clauwaert et al (2009) was used. The electrolyte (400 ml) was sparged with N 2 and pumped through cathode and anode in a separate recirculation mode at 24 ml min -1 .…”
Section: Microbial Electrolysis Cell Construction and Operationmentioning
confidence: 99%
“…In contrast with microbial fuel cells (MFCs), in which electrical energy can be extracted from the electrical circuit, one needs to supply electrical energy to the electrical circuit of an MEC by means of a power source. MECs have been used for the chemical reduction of nitrobenzenes (Mu et al 2009b), for the decolorization of azo dyes (Mu et al 2009a) and for the biologically catalyzed reduction of nitrate and TCE in a biocathode (Aulenta et al 2008;Clauwaert et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The influence of the cathode potential [5], the pH [6], or the conductivity [7] were assessed and microbial community analyses was shown a highly diverse community, suggesting a potential key role of Proteobacteria [8]. In addition to the only scattered information from the engineering perspective, the underlying fundamentals of the microbial extracellular electron transfer (EET) are still untapped.…”
Section: Introductionmentioning
confidence: 99%